Sistem Informasi Administrasi Pembayaran SPP Berbasis Website - Yahfizham Yahfizham; Lili Saputri; Mirna Annifah Hsb (Lembaga Pengembangan Kinerja Dosen, 2024)
The web-based Educational Development Contribution (SPP) Payment Administration Information System is a technology solution designed to make it easier to manage the administration of tuition fees within educational institutions. This system adopts a web-based approach to provide easy and transparent access for all stakeholders, including parents or guardians of students, administrative staff, and other related parties. The advantage of this system lies in its ability to carry out online payment transactions via a web platform, making it easier for people parents or guardians of students to pay tuition fees from anywhere and at any time. This system also provides automatic notifications to remind parents or guardians of students regarding payment due dates, reducing the risk of late payments. Data security is the main focus in designing this system. By using effective web security protocols, it is hoped that the implementation of this Web-Based Tuition Fee Administration Information System can bring significant benefits in increasing operational efficiency, transparency and ease of access in managing the administration of tuition fee payments in educational institutions.